Map Draw Competence. Theoretical Basis and the Design of a Competence Model - Frank, Friedhelm; Obermaier, Gabriele; Raschke, Nicole (Journal of Geography Education, 2010)
In this article some relevant theoretical considerations about map drawing are outlined. This includes aspects e.g. from writing competence and from geographical education. In chapter 3 results of international empirical studies to map drawing competence are discussed. Considerations about a competence model are made in chapter 4. On this basis an empirical study is planned, which is outlined in chapter 5.